2010
DOI: 10.1001/archgenpsychiatry.2010.60
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Compulsivity of Drug Abuse on Dopaminergic Modulation of Attentional Bias in Stimulant Dependence

Abstract: Context There are no effective pharmacotherapies for stimulant dependence but there are many plausible targets for development of novel therapeutics. We hypothesized that dopamine-related targets are relevant for treatment of stimulant dependence, and there will likely be individual differences in response to dopaminergic challenges. Objective To measure behavioral and brain functional markers of drug-related attentional bias in stimulant-dependent individuals studied repeatedly after short-term dosing with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 110 publications
5
92
2
Order By: Relevance
“…The whole-brain analyses identified frontal, cingulate, parietal, and temporal cortical activations that mirrored a subset of the brain areas involved in the patterns of activation identified by the ICA. The observed mass univariate whole-brain activations related to cocaine use words share dorsal, medial and inferior frontal, and temporal, parietal, and posterior cingulate cortical activations with that of a previous fMRI study of attentional bias for drug-related words in stimulant-dependent individuals (Ersche et al, 2010). The posterior cingulate, medial and inferior frontal cortex, and cerebellum activations are shared by cigarette smokers exposed to smoking cues (Wilson et al, 2012).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The whole-brain analyses identified frontal, cingulate, parietal, and temporal cortical activations that mirrored a subset of the brain areas involved in the patterns of activation identified by the ICA. The observed mass univariate whole-brain activations related to cocaine use words share dorsal, medial and inferior frontal, and temporal, parietal, and posterior cingulate cortical activations with that of a previous fMRI study of attentional bias for drug-related words in stimulant-dependent individuals (Ersche et al, 2010). The posterior cingulate, medial and inferior frontal cortex, and cerebellum activations are shared by cigarette smokers exposed to smoking cues (Wilson et al, 2012).…”
Section: Discussionsupporting
confidence: 67%
“…For nicotine-dependent individuals, the level of attentional bias for smoking-related cues was positively correlated with activation of the limbic, paralimbic, and occipital brain regions associated with emotional salience, memory recall, interoceptive states, and visual processing (Janes et al, 2010). Stimulant-dependent individuals exhibited a significant attentional bias for drug-related word stimuli that was significantly correlated with greater activation of the left ventral prefrontal cortex and cerebellum (Ersche et al, 2010). Moreover, the right dorsal anterior cingulate cortex response to cocaine use-related stimuli predicted recent cocaine use at 3-month follow-up in treatment-engaged cocaine-dependent individuals (Marhe et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…A study in non-treatment seeking stimulant-dependent individuals 108 showed that the dopamine D2/3 receptor agonist pramipexole had different effects on psychological performance in a Stroop task and related functional MRI measures in individuals with high drug-related compulsivity versus individuals with low drug-related compulsivity. If this finding is replicated with cocaine and in people with other drug dependencies, it might lead to a more sophisticated view of dopamine in addiction and, potentially, to targeted interventions such as dopamine-promoting agents in people with addiction who exhibit impulsivity.…”
Section: Does Dopamine Have Other Roles?mentioning
confidence: 99%
“…Leyton et al (2002) showed that even in healthy subjects the variability in dopamine response to amphetamine relates to subjective ratings of "wanting". Franken et al (2004) showed that the dopamine receptor antagonist haloperidol can reduce attentional bias to drug cues amongst addicts, and Ersche et al (2010) showed that the effect of such dopaminergic manipulations (both agonistic and antagonistic) varies with compulsivity. The effect of haloperidol in the former and amisulpiride in the latter, both rather selective D 2 antagonists, is surprising given the drug-induced reductions in D 2 receptors (see above).…”
Section: Individual Variability In Addiction Vulnerabilitymentioning
confidence: 99%